Enantioselective construction of branched 1, 3-dienyl substituted quaternary carbon stereocenters by asymmetric allenyl Claisen rearrangement. Issue 80 (19th September 2016) - Liu, Yangbin; Hu, Haipeng; Lin, Lili; Hao, Xiaoyu; Liu, Xiaohua; Feng, Xiaoming
Abstract : The enantioselective Claisen rearrangement of allenyl vinyl ethers was realized to access branched 1, 3-dienyl-substituted all-carbon quaternary stereocenters using a Ni II – N, N ′-dioxide complex. Abstract : The availability of enantiomerically enriched 1, 3-dienyl substituted quaternary stereocenters is highly valuable for the synthesis of complex natural compounds. Despite great advances in the area of construction of alkenyl-substituted types, a general, practical catalytic system that works for enantioselective formation of 1, 3-diene derivatives still remains to be developed. Herein, we disclose the first asymmetric Claisen rearrangement of allenyl vinyl ethers to access optically active β-ketoesters, containing branched 1, 3-butadienyl substituted stereocenters. A variety of substrates bearing a range of useful functional groups were well tolerated, thus affording the corresponding products with excellent enantioselectivities (up to 99% ee) and high yields (up to 91%).